LGBTQIA+ individuals' experiences with intimate partner violence and perceptions of victim services - Bates, Kathy (Violence and victims, 2024)
This study explored lived experiences of LGBTQIA+ survivors of intimate partner violence (IPV). Seven participants completed a one-on-one, in-depth interview to share their experiences of IPV and any internal or external factors that influenced whether they sought support services or reported victimization. Thematic analysis revealed four overarching themes: (a) health complications, (b) coping mechanisms, (c) barriers to seeking professional help, and (d) suggestions for professionals. Results contribute insight into internal and external barriers LGBTQIA+ IPV survivors face when accessing support services and outline practical approaches for professionals providing support to LGBTQIA+ IPV survivors.